مساهمة الجامعة في تحقيق وعي الطالب بمهن الإعلام و الإتصال دراسة ميدانية بكلية العلوم الاجتماعية و الإنسانية بجامعة محمد الشريف مساعدية ـ سوق أهراس - بلعيفة ريمة; ملايكية سيليا (My University, 2022)
Study Summary: This study aims to understand the university's position and role in raising awareness, and its contribution to student awareness of media and communication professions. This study addresses an important problem centered around assessing the extent of the university's contribution and the role it plays in raising awareness of media and communication professions. The theoretical aspect of the study addressed the concept of higher education, which represents the type of training offered at the post-secondary level, as well as the concept of media and communication professions, which require expertise and training through the dissemination and presentation of news to the public through specialists. Within this framework, this study sought to identify the role played by the university in raising awareness among students at the Faculty of Social and Human Sciences in Souk Ahras, by posing the following central question: How does the university contribute to raising students' awareness of media and communication professions? This question then led to sub-questions: How does university education contribute to introducing students to media and communication professions? How does the university contribute to supporting students toward a media and communication career? What are the obstacles that prevent the university from contributing to connecting students with career prospects in the fields of media and communication? The methodology adopted in this study is descriptive. The questionnaire was used as the primary tool in the study to collect field data, distributed to a stratified sample of 55 students. Interviews were used as a supporting tool for the questionnaire and to obtain more accurate information. Regarding the practical aspect, a set of conclusions were reached: - The college's role in raising awareness is based on the quality training of students. - The college focuses more on theoretical training than practical training. - The College of Social and Human Sciences faces numerous difficulties, including a shortage of professors and a lack of pedagogical resources. - Agreements between the college and economic institutions exist, but they are not being implemented to the required level. - The college seeks to develop and modernize by requesting the opening of new specializations in the field of media and communication, at the undergraduate and master's levels, to respond to the reality of the specialty and its future prospects. - The college lacks a real connection to the labor market. The college trains a large number of students, while job opportunities and employment opportunities for these graduates in their specializations are relatively limited. - Students are not informed about the existing specializations and professions they may pursue in the future. - Activities directed at students to introduce them to the field of humanities, the specialization of media and communication, and the professions that the specialization offers are very limited and insufficient. They consist only of open doors for those who have passed the baccalaureate exam, and sometimes an orientation lecture for new students arriving at the college. ----------------------------------------------- ملخص الدراسة: تهدف هذه الدراسة إلى معرفة مكانة الجامعة ودورها في زيادة الوعي ،ومساهمة الجامعة في تحقيق وعي الطالب بمهن الإعلام والاتصال، و ذلك في إطار معالجة إشكالية مهمة تتمحور حول تقييم مدى مساهمة الجامعة وما الدور الذي تلعبه في زيادة الوعي بمهن الإعلام و الاتصال. حيث تعرضت الدراسة في جانبها النظري لمفهوم التعليم العالي، الذي يمثل نمط التكوين الذي يقدم على مستوى ما بعد التعليم الثانوي، وكذا مفهوم مهن الإعلام والاتصال الذي يتطلب الخبرة والتدريب عن طريق نشر الأخبار وتقديمها للناس عبر متخصصين، و في هذا الإطار جاءت هذه الدراسة للتعرف على الدور الذي تلعبه الجامعة في زيادة الوعي لدى طلبة "كلية العلوم الاجتماعية و الإنسانية بسوق أهراس، من خلال طرح التساؤل المركزي التالي: كيف تساهم الجامعة في زيادة وعي الطلبة بمهن الإعلام و الاتصال ؟ وقد تفرعت منه تساؤلات فرعية : كيف يساهم التكوين الجامعي في تعريف الطالب بمهن الإعلام والاتصال؟ كيف تساهم الجامعة في مرافقة الطالب نحو مهنة الإعلام والاتصال؟ ما هي العوائق التي تحول دون مساهمة الجامعة في ربط الطالب بآفاق مهنية في تخصصي الإعلام و الاتصال ؟ أما عن المنهج المعتمد في هذه الدراسة هو المنهج الوصفي. كما تم الإعتماد على الإستمارة كأداة رئيسية في الدراسة لجمع البيانات ميدانيا ، حيث وُزعت على عينة طبقية تكونت من 55 مفردة من الطلبة ، و تم الإستعانة بالمقابلة كأداة داعمة للاستمارة و للتوصل إلى معلومات أدق. أما بالنسبة للجانب التطبيقي فقد تم التوصل إلى مجموعة من النتائج : - دور الكلية في تحقيق الوعي مبني على التكوين الجيد للطلاب . - تركز الكلية على التكوين في الجانب النظري أكثر من الجانب الميداني . - تواجه كلية العلوم الاجتماعية و الإنسانية العديد من الصعوبات تمثلت في : نقص الأساتذة ، نقص الوسائل البيداغوجية ...إلخ. - وجود اتفاقيات مبرمة بين الكلية والمؤسسات الاقتصادية، لكنها غير مفعّلة بالمستوى المطلوب . - تسعى الكلية للتطوير و التحديث، بطلب فتح تخصصات جديدة في مجال الإعلام والاتصال، في طوري الليسانس و الماستر بما يستجيب لواقع التخصص و آفاقه المستقبلية . - ليس هناك ارتباط فعلي للكلية بسوق العمل، إذ تكوّن الكلية أعداد كبيرة من الطلبة بينما تعتبر فرص العمل و الحصول على الوظائف لهؤلاء المتخرجين في تخصصهم محدودة نسبيا . - لا يتم تعريف الطلبة بالتخصصات و بالمهن الموجودة، التي يمكن أن يتوجهوا إليها مستقبلا . - الأنشطة الموجهة للطلبة في التعريف بميدان العلوم الإنسانية، و بتخصص الإعلام والاتصال و بالمهن التي يوفرها التخصص محدودة جدا وغير كافية ، فهي تتمثل فقط في الأبواب المفتوحة لصالح الناجحين في البكالوريا ، وأحيانا محاضرة توجيهية لصالح الطلبة الجدد الوافدين على الكلية .
Keywords: الجامعة وعي الطالب بمهن الإعلام و الإتصال